Comparison of short-term and long-term neoadjuvant hormone therapy prior to radical prostatectomy: a systematic review and meta-analysis. (4th March 2022) - Katayama, Satoshi; Mori, Keiichiro; Pradere, Benjamin; Mostafaei, Hadi; Schuettfort, Victor M.; Quhal, Fahad; Motlagh, Reza Sari; Laukhtina, Ekaterina; Grossmann, Nico C.; Rajwa, Pawel; Aydh, Abdulmajeed; König, Frederik; et al.
Abstract: Purpose: This study aimed to evaluate the efficacy of long-term neoadjuvant androgen-deprivation therapy (ADT) before radical prostatectomy (RP). Methods: We conducted meta-analyses and network meta-analyses, which included randomized controlled trials that assessed patients with prostate cancer (PC) who received either short-term (<6 months) or long-term (≥6 months) neoadjuvant ADT before RP. Results: Thirteen articles with 2778 patients were eligible for analysis. Short-term neoadjuvant ADT was neither associated with biochemical recurrence (OR 1.19, 95% CI, 0.93–1.51, p  = 0.17), metastasis (OR 0.73, 95% CI, 0.45–1.19, p  = 0.21), nor overall mortality (OR 0.72, 95% CI 0.43–1.21, p  = 0.22); no study investigated survival outcomes in patients on long-term neoadjuvant ADT. In terms of pathologic outcomes, long-term neoadjuvant ADT was significantly associated with a reduced risk of positive surgical margin (SM) and an increased rate of organ-confined disease (OCD) compared to short-term neoadjuvant ADT (OR 0.56, 95% CI 0.39–0.80, p  = 0.001, and OR 1.48, 95% CI 1.10–1.99, p  = 0.009, respectively). These findings were confirmed in the network meta-analyses. Meanwhile, only a non-significant trend favoring long-term neoadjuvant ADT was observed for pathologic complete response (OR 1.98, 95% Crl 1.00–3.93). Conclusion: Long-term neoadjuvant ADT was associated with more favorable pathologic outcomes, but whether these findings translate into favorable survival outcomes still remains unproven due to very limited evidence. Since there are no reliable survival data, long-term neoadjuvant ADT before RP should not be used in clinical practice until more robust evidence arises from ongoing trials.